Impacto das práticas ESG na percepção dos trabalhadores: uma análise das práticas sociais corporativas - Paulo, Thaís Pereira (Universidade Federal de São Carlos, 2023)
The social practices of companies have become increasingly relevant to competitiveness in the business landscape, aiming to reconcile business success with the promotion of societal well-being through actions to improve social conditions, sustainable development, and stakeholder trust. The objective of this research was to understand how the main social practices adopted by companies affect workers' perception and engagement. To achieve this, a case study was conducted through interviews with employees of a service sector company. The results demonstrated that the majority of employees are aware of and engaged by the company's social practices, with a significant emphasis on actions related to Professional Development, Health and Well-being, Social Investment, and Equal Opportunity, respectively. It was concluded that there is a preference among workers for initiatives focused on professional development and career planning.
Impact of ESG practices on workers' perception: an analysis of corporate social practices
Keywords: Práticas sociais; Responsabilidade social corporativa; Fatores ESG; Social practices; Corporate social responsibility; ESG factors; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA DO PRODUTO